PERLINDUNGAN ANAK DI LUAR NIKAH DALAM HUKUM NEGARA DAN HUKUM ISLAM (Perspektif Hakim Pengadilan Agama Parepare) - Fikri Fikri; Budiman Sulaeman; Andi Bahri (DIKTUM: Jurnal Syariah dan Hukum, 2014)
One of the purpose of protection and maintanance maqasid al-shariah realize lineage (descent), protection lineage based maqasid al-shariah, Allah as the legislator has prescribed any marriage law, a law that can be able to organize ang arrange an orderly nasab and surely, determination maqasid al-shariah in a marriage that is not accounted for by consideration of the principles of benefit for the registrate to uphold justice and the rule of law; the marriage is not registrated that it is too possible to registrated without the necessary repeated marriage, so that the benefits of the more dynamic registration of marriage any one be discriminated againts, so can be easily children and wife get the protection of civil rights. Marriage if it is possible to registrate, but not registrated is actually obscure the values of justice and maslahat in maqasid al-shariah. Saveral regulatory laws that exist in the Republic of Indonesia, is no exception of UU RI No. 1 Tahun 1974 concerning marriage can be applied elasticly, reflecsibly and dynamicly, rather than the reserve applied in staticly, rigidly and descructively that people are not discriminated againts in realizing values of protection, justice and rule of law; children born in marriage unattended or not registrated not seen let alone considered child out of marriage, not in the block to get its civil rights, but the goverment as a law enforcement and legislatory enforcement make registrated that marriage is not registrated.